2018
DOI: 10.1039/c8nj02183j
|View full text |Cite
|
Sign up to set email alerts
|

Palladium immobilized on in situ cross-linked chitosan superfine fibers for catalytic application in an aqueous medium

Abstract: Chitosan composite superfine fibers with a diameter of 321 ± 99 nm were prepared by electrospinning with PEO as the co-spinning polymer and itaconic acid as the in situ cross-linking agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The results are summarized in Table 2. Methyl acrylate is typically added in excess [37] to compensate evaporation, moreover unreacted iodobenzene in the reaction mixture causes high leaching of palladium from the catalyst [38]. Experiments with various solvents (entry 1-10) revealed that dimethylacetamide (DMA) was the most efficient solvent (entry 1, 3.6% yield).…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
“…The results are summarized in Table 2. Methyl acrylate is typically added in excess [37] to compensate evaporation, moreover unreacted iodobenzene in the reaction mixture causes high leaching of palladium from the catalyst [38]. Experiments with various solvents (entry 1-10) revealed that dimethylacetamide (DMA) was the most efficient solvent (entry 1, 3.6% yield).…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
“…Only few polymers, however, can be electrospun from aqueous solutions or low-toxic solvents. A typical example of a water-soluble polymer is poly(ethylene oxide) (PEO) [6,7], which can also be used as a spinning agent for a number of other (bio-)polymers that are not electrospinnable solely [8,9]. Amongst the water-resistant polymers, polyacrylonitrile (PAN), which can be dissolved in dimethyl sulfoxide (DMSO), is often used [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Later, Liang et al used itaconic acid (IA) as a cross-linking agent to cross-link CS/PEO nanofibers based on the reaction between the amino groups on CS and carboxyl groups on IA. 149 Furthermore, first by immersing cross-linked fibers in an Na 2 PdCl 4 aqueous solution, and then by reducing the Pd 2+ into Pd 0 species with the addition of hydrazine (a strong reductant), a Pd-immobilized composite nanofiber membrane having catalytic activity was prepared. In 2018, for the first time, Lee et al 150 produced an antiadhesive barrier composed of cartilage acellular matrix (CAM)/cross-linker nanofibers by e-spinning and cross-linking.…”
Section: Classification and Mechanismmentioning
confidence: 99%